Healing the self through spirituality in K.S Maniam's Between Lives - Awang, Mohammad Ewan; Omar, Noritah (Universiti Putra Malaysia Press, 2016)
The quest for a meaningful life and selfhood is one of the main themes in the works of K.S Maniam, a Malaysian Literature in English author. The main characters in Maniam’s works often yearn for an inner fulfillment and enlightenment that cannot be solely addressed through the socio-political and economic means. Thus, issues such as a sense of displacement, anxiety and alienation that haunt the Malaysian Indians in Maniam’s works are not just common features of postcolonial and diasporic conditions. Rather, they are symptomatic of an existential crisis. This article explores how spirituality provides a source of healing to Sumitra, the protagonist of his novel Between Lives. It uses Advaita Vedanta, an Indian philosophy to understand the genesis of Sumitra’s existential crisis and how she can surmount it. In this novel, Maniam uses recurring motifs that eschew subject-object duality such as rites of passage, excursions and mystical experiences. These motifs reflect the concept of “oneness” of Advaita Vedanta that stresses true self (Atman) transcends materialism and corporeality. Through her spiritual journey, Sumitra critically re-examines her misidentification with the ego-identity and gains insight into the true nature of “self” and “reality”. Consequently, Sumitra finds a more viable sense of selfhood through the Hindu spiritual concept of Atman. Finally, this study suggests that spirituality provides a more dynamic view of the Malaysian Indian identity construction.